DEVELOPING STUDENTS’ CREATIVE THINKING THROUGH CREATIVE WRITTEN ASSIGNMENTS IN THE NATIVE LANGUAGE SUBJECT - Jaxongirova Sanobarxon Dilmurodjon qizi (International Journal of Literature and Language Studies, 2026)
This article examines the issue of developing students’ creative thinking through creative written assignments in the native language subject. The article analyzes the pedagogical significance of creative written work and its role in forming students’ imagination, fantasy, logical thinking, and independent thinking skills. In addition, methods such as free writing exercises, creating stories based on pictures, compositions, essays, dramatic scenes, and writing games are considered with examples. The results of the study show that the systematic use of creative written assignments in the native language subject not only develops students’ language skills, but also helps to form them as creative, independent, and logically thinking individuals.